KEBIJAKAN PEMERINTAHAN DAERAH CIREBON DALAM PENERAPAN SANKSI BAGI UMKM YANG MELAKUKAN PENCEMARAN TERHADAP LINGKUNGAN HIDUP - Zauhair, Muhammad; Suryadi, Suryadi; Sholihah Hamid, Iim Imroatus; Khalimy, Akhmad (Jurnal Res Justitia: Jurnal Ilmu Hukum, 2025)
The existence of human life is highly dependent on environmental conditions. Thus, the environment has an important role in the survival of society. However, humans need a business as an effort to survive. The existence of micro, small, and medium enterprises (MSMEs) is the largest part of the national economy. In Cirebon Regency itself, there are still economic activities that cause air pollution. How is the implementation of the Cirebon Regency Regional Government policy in an effort to tackle air pollution. based on the scale of micro, small and medium enterprises based on Law Number 32 of 2009 and how the application of sanctions by the Cirebon Regency Regional Government in overcoming air pollution. The purpose of this study is to determine the policy and implementation of sanctions carried out by the Cirebon Regency Regional Government in overcoming air pollution. This research method is normative juridical research, through a statutory approach and then described descriptively analytically. The results showed that the Cirebon Regency Regional Government conducted an environmental pollution program to tackle air pollution through two major sub-districts, namely first measuring air quality to find sources of pollution, second controlling pollution and environmental damage. The application of sanctions by the Environmental Service to air pollution perpetrators has not yet reached criminal sanctions because it does not yet have an Environmental Supervisory Officer. Sanctions carried out by the Service are administrative sanctions or commonly called reprimands. The Cirebon Regional Government requires business owners to have a UKL-UPL permit which is used as the basis for an environmental permit. The government is also obliged to preserve the environment in the Cirebon area.